823. Characteristics, Comorbidities, and Medication Burden among People Living with HIV in the U.S. Medicare Program. (4th December 2021) - Li, Pengxiang; Ladage, Vrushabh P; Mao, Jianbin; Prajapati, Girish; Watson, Dovie L; Gross, Robert; Doshi, Jalpa A
Abstract: Background: Among the 1.2 million people living with HIV (PLWH) in the U.S., many are covered by Medicare, a federally funded health insurance program for elderly (≥65 years) and disabled (< 65 years) individuals. Medicare has emerged as a major source of HIV care for PLWH. Given limited research in this population, a better understanding of patient characteristics, comorbidities, and comedication use among PLWH in the Medicare program is needed to help optimize clinical care. Methods: A retrospective claims analysis of a national cross-sectional sample of fee-for-service (FFS) Medicare beneficiaries with continuous medical and prescription coverage in 2018 was conducted using 100% Medicare administrative claims. The PLWH group included individuals with ≥1 HIV diagnosis code in medical claims and ≥1 pharmacy claim for an anchor antiretroviral (ARV) drug (i.e., NNRTI, PI or InSTI) in 2018. The comparison group included a random sample of Medicare beneficiaries without HIV (PLWoH). Sociodemographic characteristics, comorbidities, and medication use were compared between PLWH and PLWoH. Results: The study sample included 86, 856 PLWH and 552, 645 PLWoH. PLWH were more likely to be younger (mean age: 57.4 vs 71.1 years and < 65 years: 72% vs 18%), male (75% vs 42%), Black (42% vs 10%), eligible for Medicare due to disability (83% vs 27%) and receiving full low-income subsidies (77% vs 31%); all p< 0.001. Prevalence of >3 comorbidities was high in PLWH (70.2%) and only slightly lower than in PLWoH (71.7% p< 0.001). Prevalence of neuropsychiatric conditions, chronic kidney disease, liver disease, COPD, hepatitis B, and hepatitis C were higher in PLWH (Figure 1). The mean hierarchical condition categories risk score was higher in PLWH vs PLWoH (1.81 vs. 1.32; p< 0.001). On average, polypharmacy was higher among PLWH vs PLWoH (annual number of unique medications: 12.6 vs. 9.4 for all drugs and 10.3 vs. 9.4 for non-ARV drugs, both p< 0.001). Figure 1. Percentage of PLWH and PLWoH with multimorbidity and selected comorbid conditions. Abbreviations: COPD=chronic obstructive pulmonary disease; GI=gastrointestinal; PLWH=people living with HIV; PLWoH=people living without HIV All p-values <0.001 except GI Disorders (p=0.14). Conclusion: In the Medicare FFS population, multimorbidity and polypharmacy were highly prevalent in PLWH despite their substantially younger age compared to PLWoH. Our findings highlight the need to consider comorbidities and comedications in HIV management including ARV regimens to minimize medication burden and drug interactions, which might improve clinical outcomes. Disclosures: Pengxiang Li, PhD, Avalon Health Economics LLC (Consultant)COVIA Health Solutions (Consultant)Healthstatistics, LLC (Consultant) Jianbin Mao, PhD, Merck (Employee)Merck (Shareholder) Girish Prajapati, M.B.B.S., MPH, Merck & Co., Inc. (Employee, Shareholder) Robert Gross, MD, MSCE, Pfizer (Other Financial or Material Support, Serve on DSMB for drug unrelated to HIV) Jalpa A. Doshi, PhD, Acadia (Consultant, Advisor or Review Panel member)Allergan (Advisor or Review Panel member)Biogen (Grant/Research Support)Boehringer Ingelheim (Other Financial or Material Support, Scientific lecture)Catabasis (Consultant)Humana (Grant/Research Support)Janssen, Inc. (Consultant, Grant/Research Support)MeiraGTX (Consultant)Merck (Grant/Research Support, Advisor or Review Panel member)Novartis (Grant/Research Support)Otsuka (Advisor or Review Panel member)Regeneron (Grant/Research Support)SAGE Therapeutics (Consultant)Sanofi (Grant/Research Support)Shire (Advisor or Review Panel member)The Medicines Company (Advisor or Review Panel member)